THE INFLUENCE OF JOB PERFORMANCE APPRAISAL, WORK EXPERIENCE AND PERSONALITY TOWARDS EMPLOYEES CAREER DEVELOPMENT PT. SUNGGONG LOGISTICS - Lisa Rahayu; Winda Widyanty (Jurnal Ilmiah Manajemen dan Bisnis, 2021)
This study aims to analyze the effect of job performance appraisal, work experience and personality on employee career development. The populations in this study were 78 employees of PT. Sunggong Logistics. The sample used was 78 employees. The sampling method uses saturated sampling technique. The data collection method used survey method with the research instrument was a questionnaire. Methods of data analysis using Partial Least Square (PLS). The results of the analysis show that the job performance appraisal, work experience, and personality have a positive and significant effect on career development. Suggestions for the management of PT. Sunggong Logistics to make improvements during job performance appraisal and to include employees in job training to improve employee skills and for all employees of PT. Sunggong Logistics for employees of PT. Sunggong Logistics is recommended to create a comfortable work environment, and build good communication for fellow employees and with the stakeholders involved.